Assistance and Training of Compost Products from Organic Waste at SMA Negeri I Tanjung Raja, Ogan Ilir, South Sumatra - Eka Sri Yusmartini Yusmartini; Mardwita Mardwita; Aseptianova Aseptianova (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2021)
The waste problem is never solved. The increase in the amount of waste every day is following the rate of population growth and activities carried out by the community. Tanjung Raja is the oldest district in Ogan Ilir Regency, South Sumatra, Indonesia. One of the educational facilities in Tanjung Raja is SMA Negeri I Tanjung Raja. Related to school environmental problems, especially to reduce the waste that will be brought to the Landfill, SMA Negeri I Tanjung Raja has not done waste sorting. During this time the garbage collected in the place that has been provided according to its designation will be thrown into the Temporary Landfill. Based on the results of observations and interviews with partners, the PKM activities that will be carried out are processing waste generated from school activities. The activity will be done by sorting the resulting waste, then continued by making compost from the leaves produced in school and also other organic waste into compost. PKM devotional activities have produced compost products from organic materials. Partners have come up with solutions to address the waste generated from daily activities and fallen leaves. The compost produced is economically valuable. This activity can overcome the problem of waste in schools and is also useful in preserving the school environment.